Individual Differences and the Ergodicity Problem. (25th September 2018) - Lowie, Wander M.; Verspoor, Marjolijn H.
Abstract: Traditional research into individual differences (ID) in second language (L2) learning is based on group studies with the implicit assumption that findings can be generalized to the individual. In this article, we challenge this view. We argue that L2 learners do not form ergodic ensembles and that language learning data lack stability. The data from our experiment show that even highly similar learners in terms of ID show clearly different learning trajectories over time; however, we did find that those who showed the greatest degree of variability gained the most in proficiency. Such findings lead to the view that group studies and individual case studies are complementary. Group studies give us valuable information about the relative weight of individual factors that may play a role in L2 development, but longitudinal case studies are needed to understand the process of individual learners' development.